2014
DOI: 10.1002/anie.201405036
|View full text |Cite
|
Sign up to set email alerts
|

The Ketene‐Surrogate Coupling: Catalytic Conversion of Aryl Iodides into Aryl Ketenes through Ynol Ethers

Abstract: tert-Butoxyacetylene is shown to undergo Sonogashira coupling with aryl iodides to yield aryl-substituted tert-butyl ynol ethers. These intermediates participate in a [1,5]-hydride shift, which results in the extrusion of isobutylene and the generation of aryl ketenes. The ketenes are trapped in situ with multiple nucleophiles or undergoelectrocyclic ring closure to yield hydroxynaphthalenes and quinolines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 44 publications
1
16
0
Order By: Relevance
“…22 In parallel, tert -butyl indolyl ynol ether 20 was synthesized according to the Sonogashira coupling condition that we reported previously. 13 Dichloromethane was added as co-solvent to improve the solubility of the starting material 19 , 23 and a 75% yield of the benzene sulfonamide (Bs) protected indole 20 was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…22 In parallel, tert -butyl indolyl ynol ether 20 was synthesized according to the Sonogashira coupling condition that we reported previously. 13 Dichloromethane was added as co-solvent to improve the solubility of the starting material 19 , 23 and a 75% yield of the benzene sulfonamide (Bs) protected indole 20 was obtained.…”
Section: Resultsmentioning
confidence: 99%
“…Ready et al 14 acetylide allows for the activation of the imine (the nitrogen atom and an oxygen of the sulfoxide).…”
Section: Scheme 30mentioning
confidence: 99%
“…This palladacycle contains an imino moiety and represents a new class of C , C ‐palladacycles, and can be utilized to develop synthetically useful reactions, in particular for N ‐containing heterocycles. However, this C , C ‐palladacycle has not been exploited to develop other organic reactions ,,. On the other hand, the Shi group demonstrated that diaziridinone exhibits high reactivity towards C , C ‐palladacycles (Scheme ) ,.…”
Section: Introductionmentioning
confidence: 99%